MEKANISME PENYELESAIAN TINDAK PIDANA PENCURIAN HASIL BUMI BERDASARKAN HUKUM MASYARAKAT ADAT OEPERIGI KECAMATAN NOEMUTI KABUPATEN TIMOR TENGAH UTARA - Luchiany Bau, Ivena O.; Rabawati, Dwityas Witarti; Samara, Finsensius (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Indonesia is a country rich in cultural diversity. The existence of various tribes, ethnicities, religions, and groups in accordance with the constitution is stated in Article 18b paragraph 2 of the 1945 Constitution. Regarding customary life, one of the villages that often still uses the customary system is Oeperigi Village. Oeperigi Village is one of the villages that has its own customary law to resolve criminal cases that occur. One of the problems often faced by the community, especially in rural areas such as Oeperigi Village is stealing agricultural products. The formulation of the problem in this study is how the mechanism for resolving criminal acts of theft of agricultural products based on customary law in Oeperigi Village, Noemuti District, North Central Timor Regency and the purpose of the problem in this study is to find out the mechanism for resolving criminal acts of theft of agricultural products based on customary law in Oeperigi Village, Noemuti District, North Central Timor Regency. The type of research used in this study is empirical legal research, the approach method used is empirical law, the data sources used in the study are primary data obtained from direct sources using data collection methods in the form of direct interviews at the research location and secondary data through literature studies. The results of this study are the mechanism for resolving criminal acts of theft of agricultural products based on customary law in Oeperigi Village, Noemuti District, North Central Timor Regency and this settlement mechanism consists of several steps, namely a report of the case from the victim to the customary leader verbally, followed by a preparation process consisting of (summoning the parties from the perpetrator, then summoning witnesses), tracing making decisions made by the customary leader which are announced publicly, then continued with the imposition of sanctions in the form of paying fines, and finally implementing peace efforts. In observing and analyzing the method of resolving criminal acts of theft of agricultural products in Oeperigi Village, it appears to use a method of resolving problems peacefully within the local community. The conclusion in the study is the mechanism for resolving criminal acts of theft of agricultural products based on customary law in Oeperigi Village and from the customary settlement mechanism in Oeperigi Village. As well as suggestions that researchers remember is that it is necessary to combine the customary law system with official legal provisions in Village Regulations.